Distribution of polycyclic aromatic hydrocarbons (PAHs) found in water along the Northern Straits of Malacca - Richard C.S, Wong,; Lai Liew, Meng,; Foong Chan, Chun, (Malaysian Journal of Science, 2008)
Marine water samples were collected during the SESMA I expedition along the northern Straits of Malacca. The route encompassed the Klang islands, the estuaries of the Selangor, Bernam and Perak rivers, Pulau Sembilan, Pulau Jarak, the estuaries of the Dinding, Matang and Gula rivers, southern Penang and Pulau Perak. Samples were collected from the surface to 1.5-2.0 m depth from a total of 18 stations located along the straits. The samples were analyzed for concentrations of a range of persistent organic polycyclic aromatics hydrocarbons (PAHs) namely: naphthalene, fluorene, anthracene, fluoranthene and pyrene. The total of these five PAHs concentrations were found to vary between 0.58 to 79.26 ÂµgL-1.